If it's not what You are looking for type in the equation solver your own equation and let us solve it.
8x+11=12x-17
We move all terms to the left:
8x+11-(12x-17)=0
We get rid of parentheses
8x-12x+17+11=0
We add all the numbers together, and all the variables
-4x+28=0
We move all terms containing x to the left, all other terms to the right
-4x=-28
x=-28/-4
x=+7
| 7x+4=31+4x | | -2(3x-4)=2x+20-2x+6 | | –5u4u=–4. | | r/16=27 | | 10n-5=23 | | 2q-6=16 | | -x+7(-5x+4)=136 | | 8(3x+2)=4(6x-4) | | x-5x=5-2x | | 6x+27=4x+7 | | -7+0.1/1.7=x | | 8+2f+9f-11=-36 | | 10(x-2)=x-19 | | 9y+7=8y-5= | | 27-9=-n | | 5x=3x+130 | | 37=u/4÷12 | | 4+5a-1=-2 | | 7x+2(-6x-17)=-69 | | -4n-8+4=-16 | | 5/b=36/45 | | 0.2857y+5=-9 | | -4(x=26)=-200 | | 9x+18=5x+34 | | 9p^2+24p+16=27 | | a2−7a+12=0 | | 21z=5,187 | | (2x-11)=57 | | 11-6x=-3(x-1)-x | | 27-x=21-4x | | 5(x-8)-5=-45 | | 7x-11=9x+7 |